2020
DOI: 10.1161/circ.142.suppl_4.219
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 219: Characterizing Covid-19 Pandemic Related Anxiety and Its Impact on Cardioprotective Health Behaviors Among Racially and Ethnically Diverse Cardiac Arrest Survivors

Abstract: Introduction: Cardiac arrest (CA) patients’ fear of contracting Coronavirus disease 2019 (COVID-19) may limit their ability or willingness to perform cardio-protective health behaviors. We assessed the association of COVID-19 anxiety with physical activity (PA), sleep, and the likelihood of seeking medical care. Methods: Between May 15-28, 2020, a month after the NYC COVID-19 pandemic peak, CA survivors from a prospective cohort were invited to particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Family members prioritized information-based interventions to alleviate uncertainty and psychological distress, which in turn could potentially improve sleep health. This finding confirms the themes from a qualitative study on in-hospital cardiac arrest, 38 a National Institute of Health funded workshop, 39 and our previous work 30 on families’ post-cardiac arrest experiences and needs. In our cross-sectional survey of a national sample (n=550) of close family members within six months of their loved one’s cardiac arrest, we identified factors influencing families’ preferences for information versus well-being needs including age over 40 years, witnessing the cardiac arrest, early caregiving, and direct discharge home.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Family members prioritized information-based interventions to alleviate uncertainty and psychological distress, which in turn could potentially improve sleep health. This finding confirms the themes from a qualitative study on in-hospital cardiac arrest, 38 a National Institute of Health funded workshop, 39 and our previous work 30 on families’ post-cardiac arrest experiences and needs. In our cross-sectional survey of a national sample (n=550) of close family members within six months of their loved one’s cardiac arrest, we identified factors influencing families’ preferences for information versus well-being needs including age over 40 years, witnessing the cardiac arrest, early caregiving, and direct discharge home.…”
Section: Discussionsupporting
confidence: 85%
“…Family members prioritized information-based interventions to alleviate uncertainty and psychological distress, which in turn could potentially improve sleep health. This finding confirms the themes from a qualitative study on in-hospital cardiac arrest, 38 a National Institute of Health funded workshop, 39 and our previous work 30 Another study found that 58% of family members of critically ill patients experienced moderate to severe sleep disturbances during hospitalization, with more information about their loved one's health being the most common suggested remedy to improve their sleep. 4 Additionally, resourceful family members reported lower levels of depression, anxiety, and sleep disturbances.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations